Achieving current rectification ratios ≥ 105 across thin films of coordination polymer. Issue 43 (16th September 2019) - Prasoon, Anupam; Dhara, Barun; Roy, Debashree; Rana, Shammi; Bhand, Sujit; Ballav, Nirmalya
Abstract : A record value of the current rectification ratio (RR ≥ 10 5 ) across molecularly doped thin films of a Cu(ii )-coordination polymer is achieved. Abstract : Downsizing coordination polymers (CPs) to thin film configurations is a prerequisite for device applications. However, fabrication of thin films of CPs including metal–organic frameworks (MOFs) with reasonable electrical conductivity is challenging. Herein, thin film fabrication of a Cu(ii )-CP employing a layer-by-layer method is demonstrated whereby a self-assembled monolayer on Au was used as the functionalized substrate. Growth of the Cu(ii )-CP at the solid–liquid interface generated open-metal Cu(ii ) sites in the thin film which were susceptible to activation by molecular dopant molecules. A significant enhancement in in-plane electrical conductivity and an unheralded cross-plane current rectification ratio (exceeding 10 5 both at room-temperature and at an elevated temperature) were achieved. Such a remarkable rectification ratio was realized, similar to those of commercial Si rectifier diodes. This phenomenon is attributed to the formation of an electronic heterostructure in the molecularly doped thin film. Molecular doping additionally transformed the interfacial properties of thin films from hydrophilic to highly hydrophobic.